2013
DOI: 10.1097/coc.0b013e31825d52f7
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Therapy Including Surgical Resection and Intraoperative Electron Radiotherapy for Recurrent or Advanced Primary Carcinoma of the Urinary Bladder or Ureter

Abstract: In patients with recurrent or advanced urothelial carcinoma, this multimodality approach yielded a low rate of recurrence within the IOERT field with acceptable toxicity. However, LR and distant relapse were common, indicating a need for better patient selection, LR therapy, and systemic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…IORT is used to deliver high doses to the tumour in an effort to improve local control. Hallemeier et al [128] reported the use of IOERT in 17 patients after maximal resection of disease. Pre- or post-operative EBRT was used in 94% of patients.…”
Section: Clinical Results With Iortmentioning
confidence: 99%
“…IORT is used to deliver high doses to the tumour in an effort to improve local control. Hallemeier et al [128] reported the use of IOERT in 17 patients after maximal resection of disease. Pre- or post-operative EBRT was used in 94% of patients.…”
Section: Clinical Results With Iortmentioning
confidence: 99%
“…Locoregional or node positive bladder cancer recurrence is treated as primary stage IV disease [11]. Hallemeier et al [14] described treating patients diagnosed with locoregional recurrence after radical cystectomy for bladder cancer, with a multimodality approach (combination pre/postoperative external beam radiation and/or surgical resection with or without concurrent chemotherapy). They found lower rates of subsequent recurrence, although distant recurrence was still common and survival benefit was not significantly increased [14].…”
Section: Local Recurrencementioning
confidence: 99%
“…Patients treated with radical cystectomy for locoregionally advanced (pT3-4) disease have a higher rate of locoregional recurrence [14]. Local recurrence following multimodality therapy (MMT) is approximately 3.9-31% at 5 years and up to 36% at 10 years [3 && , [8][9][10].…”
Section: Local Recurrencementioning
confidence: 99%
“…From the literature databases, 15 studies using IORT by brachytherapy implants or electrons were selected for this review [3549] (Table 3). Brachytherapy was the most used intra-operative modality and was employed either as a single treatment or as a boost dose combined with EBRT.…”
Section: Bladder Cancermentioning
confidence: 99%